2019
DOI: 10.1039/c9cc06961e
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced in situ detection and imaging of lipids in biological tissues by using 2,3-dicyanohydroquinone as a novel matrix for positive-ion MALDI-MS imaging

Abstract: DCH (2,3-dicyanohydroquinone), a fluorescent dye, was reported as a novel and powerful (+) MALDI matrix for lipid tissue imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 20 publications
2
25
0
2
Order By: Relevance
“…According to previous studies, , the absorption spectra of the CA, SA, and FA solutions were measured on a Jasco UV–vis spectrometer (Model V-550, Tokyo, Japan). Solid-phase UV–vis absorption spectra of CA, SA, and FA were acquired on a UV-3600 Plus spectrophotometer (Shimadzu, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…According to previous studies, , the absorption spectra of the CA, SA, and FA solutions were measured on a Jasco UV–vis spectrometer (Model V-550, Tokyo, Japan). Solid-phase UV–vis absorption spectra of CA, SA, and FA were acquired on a UV-3600 Plus spectrophotometer (Shimadzu, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…2,3-Dicyanohydroquinone (DCH) is originally known as a fluorescent dye and was applied by Liu and coworkers [41] as a new matrix for imaging of lipids in biological tissues. In contrast to commonly used matrices, more lipids could be detected from mouse brain and germinating Chinese yew seed tissue sections in positive ion mode.…”
Section: Rationally Designed and Synthesized Novel Matricesmentioning
confidence: 99%
“…To ensure and improve the ionization efficiency of 2-HG from glioma tissue microenvironment for the detection on a MALDI mass spectrometer, the selection and application of matrix is one of the most essential steps. 28 In a previous study, 1,5-DAN was reported as the most efficient matrix to detect 2-HG in glioma tissues compared to other matrices, including 2,5-dihydroxybenzoic acid (DHB), maleic anhydride proton sponge (MAPS) and 9-aminoacridine (9-AA). 20 However, 1,5-DAN is a well-known cancerogen.…”
Section: Selection and Optimization Of Matrix For 2-hg Detectionmentioning
confidence: 99%